2008
DOI: 10.1002/eat.20549
|View full text |Cite
|
Sign up to set email alerts
|

Implications of starvation‐induced change in right dorsal anterior cingulate volume in anorexia nervosa

Abstract: Objective Converging evidence suggests a role for the anterior cingulate cortex (ACC) in the pathophysiology of anorexia nervosa (AN). This study sought to determine whether ACC volume was affected by starvation in active AN and, if so, whether this had any clinical significance. Method Eighteen patients with active AN and age- and gender-matched normal controls underwent magnetic resonance imaging (MRI). Sixteen patients (89%) with AN had intelligence quotients (IQ) testing at intake, 14 (78%) had repeat MR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
72
2
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(85 citation statements)
references
References 60 publications
7
72
2
4
Order By: Relevance
“…While these studies 230 suggest altered pMFC functioning in AN, the direction of group differences vary and the possible 231 interpretations range from altered conflict monitoring, excessive cognitive control and increased 232 neural efficiency. Structurally, volume reductions in the ACC (including portions of the pMFC) in 233 acutely ill AN have been related to deficits in perceptual organization and conceptual reasoning, 234 while the degree of normalization during treatment was linked to clinical outcome (54). Using SPECT, 235 reduced regional cerebral blood flow in the dACC extending into the pre-SMA was observed during 236 the acute phase of the illness and after weight recovery (55).…”
Section: Imaging Data 187mentioning
confidence: 99%
“…While these studies 230 suggest altered pMFC functioning in AN, the direction of group differences vary and the possible 231 interpretations range from altered conflict monitoring, excessive cognitive control and increased 232 neural efficiency. Structurally, volume reductions in the ACC (including portions of the pMFC) in 233 acutely ill AN have been related to deficits in perceptual organization and conceptual reasoning, 234 while the degree of normalization during treatment was linked to clinical outcome (54). Using SPECT, 235 reduced regional cerebral blood flow in the dACC extending into the pre-SMA was observed during 236 the acute phase of the illness and after weight recovery (55).…”
Section: Imaging Data 187mentioning
confidence: 99%
“…More recent studies revealed selective GM reductions in AN patients [25][26][27][28][29][30][31]. Whether this reduction is reversible upon weight gain is under discussion [23,[25][26][27][28][29][30][31][32][33][34]. Voxel-based morphometry (VBM) studies reported GM decreases predominantly in the cingulate cortex and in the temporoparietal association cortex [25][26][27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 95%
“…Early neuroimaging studies found inconsistent results of brain volume changes, reporting a decrease for the gray matter (GM) and white matter (WM) [21][22][23], or for the WM only [24]. More recent studies revealed selective GM reductions in AN patients [25][26][27][28][29][30][31]. Whether this reduction is reversible upon weight gain is under discussion [23,[25][26][27][28][29][30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 97%
“…Studies have utilised structural [positron emission tomography (Gordon, Lask, Bryant-Waugh, Christie, & Timimi, 1997;Gordon, Dougherty, et al, 2001), single-photon emission computed tomography (Kojima et al, 2005;Lask et al, 2005) and magnetic resonance imaging (McCormick et al, 2008;Castro-Fornieles et al, 2009)] and functional imaging (Uher et al, 2005;Wagner et al, 2007;Zastrow et al, 2009). There is also a large body of positron emission tomography and single-photon emission computed tomography evidence indicating abnormal neurotransmitter systems (serotonin and dopamine) in AN (Audenaert et al, 2003;Frank et al, 2005;Bailer, Frank, Henry, Price, Meltzer, Mathis, et al, 2007;Galusca et al, 2008).…”
Section: Introductionmentioning
confidence: 97%